2019
DOI: 10.3892/mmr.2019.10526
|View full text |Cite
|
Sign up to set email alerts
|

N‑acetyl cysteine inhibits lipopolysaccharide‑induced apoptosis of human umbilical vein endothelial cells via the p38MAPK signaling pathway

Abstract: lipopolysaccharide (lPS) can regulate the expression of apoptotic factors, including caspase-3, Bcl-2 and Bcl-2-associated X protein (Bax). nitric oxide (no) plays an important role in apoptosis. n-acetyl cysteine (nac) has been shown to exhibit antioxidant effects in vitro. However, the effects of nac on lPS-induced apoptosis of human umbilical vein endothelial cells (HuVecs) and the associated mechanisms are not well characterized. The present study explored the effect of nac on lPS-induced apoptosis of HuVe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…Although, much has not been reported on effect of phthalates on sulphydryl, the result of the present study is an indication that DEHP may have caused the observed effect. This supports our hypothesis that oxido-nitrergic stress may serve as a common mediator of DEHP-cytotoxicity also purported by Huang et al (2010) and Amara et al (2020) NAC is a known precursor for GSH synthesis and scavenges ROS (Wang et al, 2014), an anti-inflammatory and antioxidant agent with the ability to inhibit NO production in several types of cells (Xiong et al, 2019). Similarly, it is known that zinc is one of the essential components of the body's most important natural antioxidant (Chian et al, 2000) and its sulphate is a potent anti-inflammatory and antioxidant agent.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Although, much has not been reported on effect of phthalates on sulphydryl, the result of the present study is an indication that DEHP may have caused the observed effect. This supports our hypothesis that oxido-nitrergic stress may serve as a common mediator of DEHP-cytotoxicity also purported by Huang et al (2010) and Amara et al (2020) NAC is a known precursor for GSH synthesis and scavenges ROS (Wang et al, 2014), an anti-inflammatory and antioxidant agent with the ability to inhibit NO production in several types of cells (Xiong et al, 2019). Similarly, it is known that zinc is one of the essential components of the body's most important natural antioxidant (Chian et al, 2000) and its sulphate is a potent anti-inflammatory and antioxidant agent.…”
Section: Discussionsupporting
confidence: 88%
“…NAC is a known precursor for GSH synthesis and scavenges ROS (Wang et al, 2014), an anti‐inflammatory and antioxidant agent with the ability to inhibit NO production in several types of cells (Xiong et al, 2019). Similarly, it is known that zinc is one of the essential components of the body's most important natural antioxidant (Chian et al, 2000) and its sulphate is a potent anti‐inflammatory and antioxidant agent.…”
Section: Discussionmentioning
confidence: 99%
“…The p38MAPK pathway is regulated through transcriptional and posttranscriptional mechanisms to affect cell death signaling as well as proapoptotic (Bax) and antiapoptotic (Bcl-2). Subsequently, the cystatin protease signaling pathway (caspase3) is altered as well, leading to apoptosis [ 15 ]. Therefore, targeting MAPK-regulated signaling pathways could potentially be an effective method in countering UVB-induced apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…As well, NAC supplementation increased levels of glutathione (GSH) in individuals with low GSH levels and improved redox homeostasis (54) . Moreover, ROS-induced mitogen-activated protein kinase (MAPK) activation could be inhibited by NAC (55) . Therefore, NAC, through decreasing lipid peroxidation, could have beneficial effects on reproductive biomarkers.…”
Section: Discussionmentioning
confidence: 99%